The frequency and affecting factors of smoking among the students at seydisehir vocational school - Kutlu, Ruhuşen; Çivi, Selma (Journal of Dependence, 2006)
Objective: The purpose of this study is to describe the prevalence of smoking among the university students and to analyze the affecting factors to smoking.Material and Methods: This descriptive and crosssectional study was carried out among 167 students attending Seydişehir Vocational School in Konya. Sociodemographic characteristics, prevalence of smoking status, smoking-related behaviors and family characteristics were examined. Statistical analyses were performed using the software packages SPSS version 10.0.Results: The prevalence of ever-smokers was 37.1% (n=62), ex-smokers 7.8% (n= 13), never smokers 55.1% (n=92), quit ratio [quit ratio is defined as the number of former smokers divided by the number of ever smokers (current and former smokers)] was 17.4%, respectively. The lowest age at starting smoking was 10 years, the highest age was 22 years and the median age was 16 years. Social environment and friend groups were the first reason to start smoking (43.5%). The ratio of smoking (91.6%) among the close friends who were ever-smokers was significantly higher than the non-smokers (p
Keywords: Nicotine addiction; university student; social environment